DDEL-08. NOVEL COMBINATION THERAPY USING PI3KINASE INHIBITION AND IMMUNE BASED THERAPY FOR THE TREATMENT OF GLIOBLASTOMA MULTIFORME. (14th November 2022) - Fonkem, Ekokobe; Rogers, Karen newell; Tobin, Richard; Das, Mita; Bowen, Sara; Tadipatri, Ramya; Healey, Debbie; Quarles, Christopher; Clark, John
Abstract: Hurdles to effective treatments for glioblastoma multiforme (GBM), the most aggressive form of brain cancer, are resistance to chemotherapy, radiation, and immune checkpoint inhibitors. GBMs, like other "difficult to treat" tumors, often over-utilize the phosphatidyl inositol 3 kinase (PI3K) pathway for survival, cell growth, and cell division, conferring both chemotherapy and radiation resistance. Furthermore, the PI3K pathway has been shown to modulate expression of Major Histocompatibility Complex (MHC) molecules, key components of immune recognition. Based on these observations, we examined the potential of a novel, small molecule PI3K inhibitor GCT.Glio.1 (NPT520-337), which was designed to cross the blood brain barrier, to increase the sensitivity of GBM to immune based therapies and radiation. We hypothesized that targeting PI3K would result in growth arrest and increase cell surface expression of MHC molecules and the PD-L1 checkpoint target. Treatment of GL261 mouse and human U251 GBM cell lines with GCT.Glio.1 caused growth arrest at the G2/M checkpoint, increased the cell surface expression of PD-L1 and MHC class II, and synergized with radiation to cause growth arrest and cell death. Based on these results we designed and performed in vivo animal studies, implanting luciferase-flagged GL261 into the caudate nucleus of C57BL6 mice. We treated the animals orally with GCT.Glio.1 followed 24 hours later by anti-PD1 therapy in repeating cycles. The treatments significantly delayed progression of the tumor when compared to no treatment or either treatment alone, with several animals exhibiting complete regression as measured by MRI and bioluminescence. In conclusion, these results indicate that GCT.Glio.1 may sensitize GBM to immune checkpoint inhibitor and/or radiation therapies. Based on our encouraging pre-clinical data and early results from pre-clinical pharmacology and safety studies, we anticipate filing a pre-Investigational New Drug application (pre-IND) as the next step toward our goal of a clinical trial using this combination therapy.